Has the consistency evaluation policy of generic drugs promoted the innovation quality of Chinese pharmaceutical manufacturing industry? An empirical study based on the difference-in-differences model - Liu, Qiang; Huang, Zhe; Mao, Zhenbin (Frontiers in Public Health, 2023)
Introduction In March 2016, the Chinese government officially launched a nationwide consistency evaluation of the quality and efficacy of generic drugs. Methods This paper conducted an empirical study using the Difference-in-Differences method to explore the effect of this policy on the innovation quality of China’s pharmaceutical manufacturing industry and further analyzed the underlying mechanism of action. Results The results of the study show that the generic consistency evaluation policy has a significant promotion effect on the innovation quality of China’s pharmaceutical manufacturing industry, and the promotion effect is the largest for non-state-owned enterprises and enterprises in the central region; in addition, the intensity of R&D capital investment and R&D personnel investment which play a mediating role. Discussion Therefore, we should fully recognize the positive effect of generic drug consistency evaluation policy on improving the innovation quality of the pharmaceutical manufacturing industry and pay attention to the necessity of regional coordination and unification in policy implementation and the formulation of supporting policy tools. This study provides empirical evidence for the implementation effect of the generic drug consistency evaluation policy, which can provide an essential reference for the further improvement of the procedure and the R&D decision-making of pharmaceutical enterprises.